Managing alliance portfolios and networks - Das, T. K. (Research in strategic alliances., 2017)
Managing Alliance Portfolios and Networks is a volume in the book series Research in Strategic Alliances that focuses on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series also includes comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series seeks to disseminate theoretical insights and practical management information that should enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances.Managing Alliance Portfolios and Networks contains contributions by leading scholars in the field of strategic alliance research. The 9 chapters in this volume deal with significant issues relating to the management of alliance portfolios and alliance networks. These issues range from value creation in alliance ecosystems, management lessons from social enterprise, and a configurational perspective on alliance management capabilities, to the competition dynamics of alliance networks, internationalization of an alliance portfolio, and structural embeddedness of alliance networks during industry convergence. The chapters contain empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on managing alliance portfolios and alliance networks.